Poetical reduplications in Alexander Vvedensky’s fiction - Tatiana V. Tsvigun (Immanuel Kant Baltic Federal University, 2021)
The article is devoted to the study of the poetics of reduplication in Alexander Vvedensky's fiction texts. The aim of this research is to analyse the functional range of reduplications at different textual levels, from the lexical to the thematic. Reduplication is understood as one of the most important tools of Vvedensky's linguopoetic experiment, aimed at the 'revision' of the ability of language to signify and represent the world and its basic semiotic principles. For Vvedensky, the non-normative punctuation of contact lexical reduplications creates prerequisites for perceiving repeated word forms as occasional homonyms, distinguishes the signified behind the signifier, and also problematizes the nature of poetic communication. On the grammatical level, reduplication creates tension between repeated grammar patterns and their lexical realisations, which allows Vvedensky to demonstrate the potential extensibility of syntactic models and make grammatical semantics a compensatory mechanism that fills the semantic void of the poetic utterance. Vvedensky's thematization of reduplication as the "doubling of the world" is a mirror, which deforms and transforms reality. Mirror semiosis illustrates the loss of iconicity by reduplication and, as a consequence, the impossibility to represent the object by its reflection. The authors conclude that on the level of vocabulary and grammar, reduplication creates dynamism in the verbal space of the text, activates its interpretation and thus creates the situation of gnoseological doubt in the adequacy of language as a means of representing the world. In the thematic field, it deprives the world of its self-identity since objects constantly multiply, lose their distinctiveness or, on the contrary, find meaning where it does not exist.